'… This is my home and my neighbourhood with my very good and not so good memories': The story of autobiographical place-making and a recent life with dementia. (January 2020) - Calvert, Lesley; Keady, John; Khetani, Beena; Riley, Cathy; Swarbrick, Caroline
As part of the wider Neighbourhoods and Dementia Study, co-researchers from the Open Doors Research Group (based in Salford, UK) produced a series of three films with the title 'The Changing Face of our Neighbourhood'. These films were subsequently placed on 'YouTube' and document co-researchers' storied experiences of Salford and the industrial, economic and social changes that have occurred over the inquiry group's lifetime. Drawn directly from this autobiographical and socio-generational work, this article focuses on the experience of lead author Lesley Calvert, who was diagnosed with dementia in 2013 and has been a member of the Open Doors Research Group since 2014. Lesley grew up and worked as a district nurse for almost 40 years, remaining close to her place of birth in Salford all her life. In this article, Lesley draws upon her autobiographical narrative which she shares in the three films to describe the intersections between biography, place-making, belonging and dementia. The article concludes with the importance of democratising the research space and why academic researchers need to create opportunities for personal stories to be told, heard and acted upon.